ONLINE COSTUMER BEHAVIOR IN FOOD TOURISM - Hanan Laras Sabrina; Arina Rahmi (Journal of Business Studies and Management Review, 2019)
The development of technology that is very fast and dynamic, can be utilized by businesses for their business development. Entrepreneurs and costumers can use technology through the internet to get any information needed without distance and time limit. Social media is one of the many online media that is a favorite of businesses because this media provides a way to get closer to costumers. In the food industry, business people keep up with using social media as a forum for the promotion of food products. Furthermore, the food products offered, especially traditional foods of an area, can be one of the efforts for the development of tourism, especially culinary tourism. From the findings of previous literature by (Blanca Garcia Henche, 2018) it is known that social media can be used as a communication strategy in tourism deals in this case regarding food tourism as a form of the tourist experience. This study aims to examine social media marketing in tourist destinations and online customer behavior in food and food tourism into a destination. This study uses a systematic literature review to identify customer behavior in marketing through social media on food products to be a choice in determining tourist destinations